Sondagem do canal banda larga sem fio: técnicas, simulação e pós-processamento de dados - Barbosa Filho, José Marcos Leal (2020)
In recent years, the demand for high data rates in wireless communications has increased. The Enhanced Mobile Broadband (eMBB), one of the use cases of fifth generation of mobile communications systems (5G), requests 20 Gbps of minimum peak data throughput using carrier aggregation technique to achieve ultra-widebands. However, wideband and ultra-wideband signals are more susceptible to time and frequency spread degradation due to signal propagation over multiple paths and relative movement between transceivers, respectively. In this context, the channel sounding is of great relevance, since it allows to estimate the characteristics of the transmission medium, enabling the conception of solutions to combat the performance degradation imposed by the communication channel. From this perspective, this work develops a research on the main wideband channel sounding techniques, taking as main objective the conception in software of a channel sounding simulator and a post-processing and analysis tool for wireless wideband channel characterization. In addition, a comparative analysis of the direct cross-correlated soundings is performed, using 6 different sequences as sounding signal. Among them are the sequences PN, Zadoff-Chu and Golay.